Adaptive legisign formation in the cross-media transformation of Riau Malay Songket into Batik - Widayanti, Eka; Muhajirin, Muhajirin (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2026)
This study examines the transformation of Riau Malay songket ornaments into batik design as a semiotic process that generates adaptive legisigns within contemporary cultural practice. Previous scholarship has largely emphasized the historical and symbolic meanings of songket within its original woven medium, leaving limited discussion on how these culturally institutionalized signs operate when transferred across material forms. Focusing on three principal motifs, Pucuk Rebung, Tampuk Manggis, and Pucuk Bersusun. This research employs an interpretive ethnographic approach combined with Peircean semiotic analysis to investigate shifts in qualisign, sinsign, and legisign functions during cross-media adaptation. Data were collected through field observations, in-depth interviews, and visual documentation in Riau. The findings reveal that adaptation does not occur as visual replication, but as a process of aesthetic reinterpretation involving simplification of form, redistribution of composition, and chromatic adjustment in accordance with batik techniques. Despite material reconfiguration, symbolic continuity is maintained through communal validation by artisans and cultural authorities. The study proposes an analytical model of adaptive legisign formation to explain how traditional visual sign retain cultural legitimacy while participating in contemporary design contexts. This research contributes to cultural semiotics by demonstrating that institutionalized signs are not bound to a single medium, but can be re-stabilized through socially regulated processes of reinterpretation.   Penelitian ini mengkaji transformasi ornamen songket Melayu Riau ke dalam desain batik sebagai proses semiotik yang menghasilkan legisign adaptif dalam praktik budaya kontemporer. Kajian sebelumnya lebih banyak menekankan makna historis dan simbolis songket dalam medium tenun aslinya, sehingga pembahasan mengenai bagaimana tanda-tanda budaya yang terinstitusionalisasi tersebut beroperasi ketika berpindah medium masih terbatas. Berfokus pada tiga motif utama Pucuk Rebung, Tampuk Manggis, dan Pucuk Bersusun penelitian ini menggunakan pendekatan etnografi interpretatif yang dipadukan dengan analisis semiotik Peirce untuk menelaah pergeseran fungsi qualisign, sinsign, dan legisign dalam proses adaptasi lintas media. Data yang diperoleh melalui observasi lapangan, wawancara mendalam, dokumentasi visual di Riau. Hasil penelitian menunjukkan bahwa adaptasi tidak berlangsung sebagai reproduksi visual semata, melainkan sebagai reinterpretasi estetis melalui penyederhanaan bentuk, redistribusi komposisi, dan penyesuaian warna sesuai karakter teknik batik. Meskipun terjadi rekonfigurasi material, kesinambungan makna tetap terjaga melalui validasi komunal oleh perajin dan otoritas budaya. Penelitian ini menawarkan model analitis pembentukan legisign adaptif untuk menjelaskan bagaimana tanda visual tradisional mempertahankan legitimasi budaya sekaligus berpatisipasi dalam konteks desain kontemporer. Temuan ini berkontribusi pada kajian semiotika budaya dengan menunjukkan bahwa tanda yang terinstitusionalisasi tidak terikat pada satu medium, melainkan dapat distabilisasi kembali proses reinterpretasi yang diatur secara social.